On the probabilistic assessment of variability in fatigue life in a near α titanium alloy Timetal 834: Crystallography of fatigue crack initiating facets. (1st October 2021) - Prasad, Kartik; Sarkar, Rajdeep; Singh, Vajinder; Ghosal, P; Bhattacharjee, Amit; Gokhale, Hina
Abstract: In the present study, variability in high cycle fatigue behaviour at five maximum stress levels of cycling, viz. 826, 778, 680, 583 and 486 MPa, have been studied on a near α titanium alloy Timetal 834. It was found that decrease in stress level of cycling resulted in increase in variability of fatigue lives. In all of the tested samples, microstructural examination of failed specimens by scanning electron microscope revealed the fatigue fracture site as facet (s). The morphology of these facets resembled to that of relatively larger primary α grain (s) in majority of the failed samples. Probabilistic assessment of fatigue lives corresponding to the stress level of 486 MPa showed three slope regions in cumulative distributive functions. These three regions complimented well with the orientations of facets i.e., facet angle to the loading axis which was determined using tilt fractography. Samples with fatigue lives 〈 10 5 cycles showed facet angle ≤ 30° to the loading axis, whereas, facet angle was found to be near 45° in longer life samples with fatigue lives 〉 10 7 cycles. This, in turn, highlighted the dominance of shear component of stress in improving the overall fatigue life in Timetal 834. It was demonstrated that life extension based on mechanism-based approach results in four-fold increase in extended life. Graphical abstract: Image, graphical abstract